Vocabulary games as a way of motivating students - Shcherbina, V. (Teaching Languages at Higher Educational Establishments at the Present Stage. Intersubject Relations, 2017)
The article is devoted to the analysis of vocabulary games as specific learning activities and the way of motivating students in their combination with the other English language teaching techniques at all the stages of an English lesson. Vocabulary games are taken into consideration as alternative to the traditional way of forming lexical competence and teaching vocabulary. They are described as the form of work designed for activating, practicing, controlling and retrieving stored vocabulary. It is shown that vocabulary games are a good way of recycling and memorizing linguistic units.Such games may help students improve their general knowledge and to be able to communicate on various subjects. Vocabulary game is viewed both as a kind of time-filler and the activity playing the central role in communicative situation created for developing learner’s communicative skills. Vocabulary games may be viewed as integral parts of other activities. They seem to be helpful for passing new lexical items from the short-term to more reliable long-term memory. It is pointed out that vocabulary games usually require somepreparation. The games make use of variety of techniques. They may be enacted around the certain topic and are based on the use of active vocabulary. It is proved that crossword puzzlesare especially time-consuming as they require more time to prepare and organize. The set of vocabulary games efficient for the development of students“ lexical competencehas been offered. It is proved that vocabulary games give learners the opportunity to sense the work of language as living communication. They help students to become more word curious and more confident in their everyday speech and writing. It is shown that vocabulary games may be based on team work in order to maximize ways of making every learner experience success. It is pointed out that some games may have quite a complicated structure consisting of a number of activities. Some of them can be used as warming-up exercises some activities can help students to integrate new knowledge into existing knowledge. The vocabulary games offered in the article may be especially efficient if there is a lot of vocabulary to review. Such activities may be challenging but they help to create learning environment which leads students to success and joy of learning. They get students motivated and make learning process more memorable and exciting.